2018
DOI: 10.1016/j.jgr.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ultrasonication-processed ginseng berry extract on the D-galactosamine/lipopolysaccharide-induced liver injury model in rats

Abstract: BackgroundAcute hepatic failure is a life-threatening critical condition associated with rapid deterioration of liver function and liver transplantation. Several studies have shown that Panax ginseng Mayer has antidiabetic and hepatoprotective effects. However, the hepatoprotective effect of ginseng berry is still unveiled. In this study, we evaluated the hepatoprotective effects of ultrasonication-processed ginseng berry extract (UGBE) on acute hepatic failure model in rats.MethodsGinseng berry extract (GBE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…A new cultivar, K-1 has been reported recently with its superior representation which has excellent root shape and strong disease resistance [ 10 ]. Apart from physical representation, chemical constituents (especially ginsenosides) existing in red ginseng berry (RGB) extract has been frequently studied [ 11 , 12 ]. However, the chemical components and biological activities of green (unripe) ginseng berry (GGB) extract are less reported as compared to RGB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new cultivar, K-1 has been reported recently with its superior representation which has excellent root shape and strong disease resistance [ 10 ]. Apart from physical representation, chemical constituents (especially ginsenosides) existing in red ginseng berry (RGB) extract has been frequently studied [ 11 , 12 ]. However, the chemical components and biological activities of green (unripe) ginseng berry (GGB) extract are less reported as compared to RGB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, some herbs in hypoglycemic granule have shown a good protective effect on the liver function . And recently, a great deal of research also indicated that the prolongation of the liver injury process will inevitably lead to changes in the liver structure and function in db/db mice .…”
Section: Discussionmentioning
confidence: 99%
“…Stagnant hydrophobic bile acids can damage the mitochondrial electron transport system and produce ROS in the liver. ROS cause an inflammatory response and alter the equilibrium between antioxidant and pro-oxidant activities [293031]. The damaged liver fails to metabolize ammonia properly and accumulates ammoniainduced type 3 HE [6].…”
Section: Discussionmentioning
confidence: 99%